Corporate Social Responsibility: What Motivates Management to Disclose? - Ling, T.C.; Sultana, Nigar (Emerald Group Publishing Ltd., 2014)
Purpose – The purpose of this paper is to provide empirical evidence on the significance of signal breaches from technical trading indicators in explaining variations in the level of corporate social responsibility disclosures (CSRD) by firms. The authors seek to determine whether firms disclose corporate social responsibility (CSR) information in a genuine attempt to report their impact on society and environment or whether firms use CSRD as a shield to legitimise their business operations. Design/methodology/approach – Signal breaches from the Moving Average Convergence Divergence and Chande’s TrendScore technical trading indicators were utilised, while the voluntary environmental and social accounting disclosure index developed by Williams (1998) was adapted to measure the extent of CSRD by Singaporean firms in 2011. Ordinary least squares regression was the principal multivariate statistical technique used to analyse the data collected. Findings – Findings of this paper indicate a positive and significant association between the number of technical indicator signal breaches for a firm and the level of CSRD by that firm, particularly in the environment, energy, human resources and products and customers categories.Research limitations/implications – The collection of CSRD information is based solely on annual reports and within the context of Singapore. Results, therefore, are not completely generalisable to different jurisdictional settings. Practical implications – Findings suggest that firms with a volatile stock price trend provide greater CSRD, possibly as a legitimacy strategy to distract or change the perceptions of investors from its current legitimacy status. Findings, therefore, highlight to regulators the need to strengthen regulatory requirements and implement stricter guidelines on CSR reporting, given the importance of CSRD to users. Social implications – Findings from this study have several implications for various stakeholders including investors, regulators and society in general. Overall, findings also suggest that stakeholders should not rely solely on CSRD in their decision-making process. Originality/value – This is the first paper that has proxied stock price movement by using breaches in technical trading indicators when examining reported levels of CSRD by firms. Moreover, results greatly build on the sparse CSR research on Singapore.